Sensorless Deadbeat Control Strategy With Adaptive Capability for PMSM Drive Machines - Mohammed, Sadeq Ali Qasem; Almuhaini, Mohammad M.; Lee, Kyo Beum (IEEE Access, 2025)
This research work designs an adaptive sensorless deadbeat control (AS-DBC) method for permanent magnet synchronous motors (PMSMs). The proposed AS-DBC effectively merges the merits of deadbeat control (DBC) for ensuring fast dynamic response while incorporating the outstanding features of adaptive control to enforce satisfactory control performance of PMSM drive systems such as insensitive to system perturbation, system mismatches, and parameter alterations, etc. Hence, merging these two methods elevates the robustness and enhances steady-state and dynamic responses. As the DBC contributes to improved dynamic response, the adaptive compensating items satisfy the practicality of the system to tolerate nonlinear behavior inherent in PMSM drives. The adaptive control terms are dynamically updated online to effectively suppress system uncertainties under severe conditions; for instance, low-speed region. The proposed AS-DBC method is then validated leveraging the PSIM simulation tool and experimentally tested using a PMSM drive setup, exhibiting superior performance in terms of precisely tracking capability covering low-, medium-, and high-speeds, and reduced estimated speed ripples compared to classical control methods.
Keywords: Adaptive capabilities; Adaptive Control; Control methods; Control strategies; Deadbeat control; Permanent Magnet Synchronous Motor; Permanent-magnet synchronous motor drives; Sensorless; Speed estimation; Work design; Adaptive control; deadbeat control; permanent magnet synchronous motors; sensorless control; speed estimation